التورق المصرفي وتطبيقاته في المصارف الإسلامية الكويتية : دراسة استطلاعية - عجمي، عبد الله فهد محمد (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2017)
The current study aimed to identify the positive and negative effects of banking foliation in Islamic banks as well as to identify the views and the impressions of researches about the effects of the banking foliation on the Islamic banks and the Kuwaiti economy. This study was applied on a sample consisting of 260 workers in Kuwait Islamic banks (Ahli United Bank, Kuwait International Bank, Kuwait Finance House, Boubyan Bank). Moreover, a questionnaire was used to measure the economic effect of the banking foliation in Kuwaiti Islamic Banks after the verification of the veracity of the questionnaire by using factor analysis and the sincerity of arbitrators. The stability of the questionnaire was confirmed by using Cronbach's alpha coefficient and the stability of mid-retail by using Spearman Brown coefficient. The results indicated that the questionnaire is characterized by a degree of validity and reliability which suitable for the purposes of the current study. Subsequently, the data was collected and analyzed, and the study showed the following results: Banking Foliation accommodates customers' need to loan and liquidity with an acceptable legal manner, as well as the banking foliation helps people to keep away from dealing with ribabased banks and helps to run huge money to their depositors. The cost of banking foliation in the Islamic banks is higher than the cost of interest in the riba-based banks. The banking foliation leads to find loan easier, and to make Islamic banking lazy in searching for acceptable alternatives in the banking industry. Therefore, it leads to increase the consumption, and contributes to rise the public debt ratios. The banking foliation is used in the sale and purchase of local goods, cement, iron, and vehicles. The banking foliation makes Islamic banks to dispense with other financing forms. It restricts the role of Islamic banks in offering cash loans and realizing gains as well as Islamic banks keep away from the task of investment mediation and the lazing of searching about new Islamic financing forms. Then, the customers of Islamic banks keep away from the real investment leading to the ending of the Islamic bank model idea. The expanding use of banking foliation in Kuwaiti Islamic banks makes the loan more easier, and increases the public debt and Inflation rates. It leads Islamic banks to keep away from their basic function.